Condensation water in heritage touristic caves: Isotopic and hydrochemical data and a new approach for its quantification through image analysis. Issue 5 (27th May 2021) - Liñán, Cristina; Benavente, José; del Rosal, Yolanda; Vadillo, Iñaki; Ojeda, Lucía; Carrasco, Francisco
Abstract: Condensation water is a major factor in the conservation of heritage caves. It can cause dissolution of the rock substrate (and the pigments of rock art drawn on it) or covering thereof with mineral components, depending on the chemical saturation degree of the condensation water. In show caves, visitors act as a source of CO2 and thus modify the microclimate, favouring negative processes that affect the conservation of the caves. In spite of their interest, studies of the chemical composition of this type of water are scarce and not very detailed. In this work we present research on the condensation water in the Nerja Cave, one of the main heritage and tourist caves in Europe. The joint analysis of isotopic, hydrochemical, mineralogical and microbiological data and the use of image analysis have allowed us to advance in the knowledge of this risk factor for the conservation of heritage caves, and to demonstrate the usefulness of image analysis to quantify the scope of the possible corrosion condensation process that the condensation water could be producing on the bedrock, speleothem and rock art. To our knowledge, this application of image analysis (relative to the condensation water in caves) is the first one of this type that has been documented. Abstract : We present a research on the condensation water in the Nerja Cave, one of the main heritage and tourist caves in Europe. The analysis of isotopic, hydrochemical, mineralogical and microbiological data and the use of image analysis have allowed us to advance in the knowledge of this risk factor for the conservation of heritage caves and to quantify the scope of the possible corrosion condensation process that the condensation water could be producing on the bedrock, speleothem and rock art.